FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI IKAN DI DESA NANGADHERO KECAMATAN AESESA KABUPATEN ENDE - Muku, Monika Natalia; Djata, Baltasar Taruma; Sedho, Yuliana (JURNAL EQUILIBRIUM, 2021)
This study aims to determine and explain the factors that influence fish production in the Nangadhero village, Aesesa District, Nagekeo Regency. The population in this study were all members of the fishing community who work as fisherman in the Nangadhero Village. Totaling 129 people. The sample in this study amounted to 98 people using simple random sampling technique in this research is by distributing questionnaires to fisherman. The data analysis technique uses Multiple Linear Regression analysis with calcutions using the SPSS 21 program. Based on the results of the analysis that has been done, this study shows that education has a negative and insignificant effect on fish production, while skillsin using fishinggear have a positive and significant effect on fish production. The results of this study can be used to formulare effective policies and strategies for activities to increase fish production and income of fishing communities in Nangadhero Village, and itis hoped that the local government can provide fishing equipment and education to improve the skills of fisherman through training programs.